Pharmacists Who Screen and Discuss Opioid Misuse With Patients: Future Directions for Research and Practice. (August 2015) - Cochran, Gerald; Field, Craig; Lawson, Kenneth
Background: Prescription opioid (PO) abuse has reached epidemic proportions in the United States, and pharmacies are locations from which these medications are often diverted. This study identifies factors associated with pharmacists who currently screen and discuss PO misuse with patients. Methods: A secondary data analysis of a cross-sectional Web-based survey that was sent to pharmacists was conducted. The survey contained items that assessed whether pharmacists currently screened and discussed PO misuse with patients along with pharmacists' attitudes and beliefs toward providing brief interventions. Multivariable models were developed which identified factors associated with pharmacists' currently screening and discussing misuse. Results: Chain setting pharmacists (odds ratio [OR] = 6.16, 95% confidence interval [CI] = 1.16-32.72) and pharmacists interested in being directly involved in PO screening and brief intervention research projects (OR = 2.06, 95% CI = 1.35-3.15) were most likely to report current screening. Pharmacists who reported currently screening for misuse (OR = 4.27, 95% CI = 2.83-6.45) and who reported wanting to help patients who misuse POs (OR = 3.03, 95% CI = 1.50-6.15) were most likely to currently discuss abuse. Conclusions: Investigators implementing pharmacy-based screening and brief intervention studies for POs should take into account practice location and pharmacists' interest in addressing PO issues.